The relationship between uric acid concentration and cardiovascular risk: Retrospective analysis of patients on hemodialysis - Radović Ana; Milinković Neda; Stošović Milan; Dopsaj Violeta; Ignjatović Svetlana (Pharmaceutical Association of Serbia, Belgrade, Serbia, 2019)
Literature data indicate that increased uric acid (UA) levels are an important risk factor for cardiovascular disease. The aim of this study was to examine the association of UA with cardiovascular risk factors in patients with hemodialysis using retrospective analysis. In 110 patients, we studied the values of basic renal function parameters, bone metabolism and cardiovascular risk factors in the period from 2010 to 2017. The results indicate a significant increase in urea (P=0.004), creatinine (P=0.028) and inorganic phosphate (P=0.001), as well as significant differences in gender (P=0.013), in risk categories defined on the basis of the UA decision limit (cut off <350 mmol/L). After controlling the effects of most parameters, statistically significant correlation coefficients were obtained for UA and urea (r=0.361; P=0.0013), creatinine (r=0.388; P=0.0005) and inorganic phosphate (r=0.366; P=0.0011). Significant regression coefficients were obtained for UA and male gender (b=-0.227, P=0.004), age (b=-0.298, P˂0.001), urea (b=0.271, P=0.005) and inorganic phosphate (b=0.232, P=0.009). The predictive value of independent parameters in relation to UA was confirmed for male gender (OR=3.595; 95% CI: 1.421-9.094; P=0.007) and inorganic phosphate (OR=14.842; 2.518-87.472, P=0.003). By Cox regression analysis of proportional hazard ratio, we obtained the most significant combined effect of the body mass index, dialysis and diastolic pressure on UA concentration in relation to the duration of hemodialysis (P <0.0001). The results of this long-term study suggest that UA can not be considered an independent cardiovascular risk factor, but that HD patients need to strategically control the level of MK in order to reduce the resulting complications, morbidity and mortality.